2020
DOI: 10.1111/imr.12848
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐intrinsic metabolic regulation of mononuclear phagocyte activation: Findings from the tip of the iceberg

Abstract: We have only recently started to appreciate the extent to which immune cell activation involves significant changes in cellular metabolism. We are now beginning to understand how commitment to specific metabolic pathways influences aspects of cellular biology that are the more usual focus of immunological studies, such as activation-induced changes in gene transcription, post-transcriptional regulation of transcription, post-translational modifications of proteins, cytokine secretion, etc. Here, we focus on me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 124 publications
(303 reference statements)
1
38
0
Order By: Relevance
“…Innate immune cells also undergo metabolic programming and use metabolic pathways to control cell fate. Bakker and Pearce provide a detailed review on the past decade of progress in understanding immunometabolism with a focus on DC and macrophage metabolism 48 . Mononuclear phagocytes are important in sampling the environment and crosstalk with neighboring cells, effectively bridging innate and adaptive immunity.…”
Section: Basic Mechanisms That Regulate Immune Metabolismmentioning
confidence: 99%
“…Innate immune cells also undergo metabolic programming and use metabolic pathways to control cell fate. Bakker and Pearce provide a detailed review on the past decade of progress in understanding immunometabolism with a focus on DC and macrophage metabolism 48 . Mononuclear phagocytes are important in sampling the environment and crosstalk with neighboring cells, effectively bridging innate and adaptive immunity.…”
Section: Basic Mechanisms That Regulate Immune Metabolismmentioning
confidence: 99%
“…Increases in lactate and pyruvate can be interpreted as increased glycolysis in patients with high CRP, perhaps driven by hypoxia of carbon flow from pyruvate to acetyl-CoA. Increased glycolysis is a metabolic consequence of both immune cell activation and hypoxemia (Frauwirth et al, 2002; Jellusova, 2020; Makowski et al, 2020; Michalek et al, 2011; van Teijlingen Bakker and Pearce, 2020). Importantly, each of these three classes of metabolites represent entry points to the TCA cycle and elevated levels of these features are consistent with mitochondrial dysfunction and decreased activity in the TCA cycle and the electron transport chain (ETC).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, monosaturated and saturated fatty acids (SFA) were highly abundant as a result of HFD feeding. Fatty acids are an important energy source and are readily taken up and stored as triacylglycerides or metabolized by immune cells upon activation [ 45 ]. It has been shown that fatty acids affect immune cell homeostasis and function via their metabolism or engagement with specific membrane receptors.…”
Section: Discussionmentioning
confidence: 99%